Heterosis for yield and yield components in some sesame (Sesamum indicum L.) genotypes - Ali, Khalafalla A. (Gezira Journal of Agricultural Science, 2013)
ABSTRACT    The objective of this study was to determine the heterotic effect for yield and yield components in some sesame genotypes. Eight sesame lines were selected as parents from the sesame breeding program, Gedarif Research Station, Agricultural Research Corporation (ARC), Sudan. The parents were crossed in all possible diallel combinations (without reciprocals) to produce 28 single-cross hybrids. The eight parents and 28 F 1 generatins were evaluated under rain for two consecutive seasons (2005 and 2006) at Gedarif Research Station. Four of the parents were released varieties viz : Ziraa-9, Kenana-2, Promo and Gedarif-1, and the other four were advanced lines. The experiment was arranged in a randomized complete block design with three replicates to elucidate heterotic effect for yield and yield components among the 36 sesame genotypes. Data were recorded on days to 50% flowering, days to maturity, plant height, number of branches/plant, number of capsules/plant,  height to first capsule, capsule length, 1000-seed weight, seed yield/plant and seed yield/ha. Heterosis was calculated as percentage increase or decrease over mid parent, corresponding better parent and standard parent, for the ten characters. Average heterosis, heterobeltiosis and standard heterosis in all characters were detected. The cross Gd2002OBN.103×Promo expressed significant negative heterosis for days to 50% flowering for the three types of heterosis, negative heterosis for days to maturity and positive heterosis for seed yield/ha, hence could be exploited for developing early maturing and high yielding varieties. Significant positive heterotic values of the three types of heterosis for seed yield/ha were shown by Gd2002SPSN.53×Gedarif-1 and Gd2002SPSN.53 ×Promo. It is concluded that further testing is needed to confirm consistency of these crosses in terms of their seed yield and stability.